Role Engagement and Anonymity in Synchronous Online Role Play - Cornelius, Sarah; Gordon, Carole; Harris, Margaret (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
Role play activities provide opportunities for learners to adopt unfamiliar roles, engage in interactions with others, and get involved in realistic tasks. They are often recommended to foster the development of soft skills and a wider perspective of the world. Such activities are widely used as an online teaching approach, with examples ranging from the simple use of email to the employment of virtual worlds and Web 2.0 technologies. This paper provides a case study of a role play activity which employs real-time anonymous discussion forums and aims to improve our understanding of effective role play and the impact of anonymity. This role play has been effective in educating learners about different perspectives on the issue of Quality in Further Education. The context and implementation of the role play are outlined, and the learners’ interactions and experiences are explored using an investigative analysis of discussion transcripts and semi-structured interviews with participants. The findings suggest that role engagement and anonymity are important components for success in synchronous online role play. Evidence is presented that provides an insight into the factors which encourage role engagement, including prior experiences and contributions from peers. The impact of anonymity is also explored since many participants did not regard the study environment as real and attempted to identify their peers.